Peran Media Sosial dalam Meningkatkan Popularitas Musik Jawa di Kalangan Generasi Muda - Herni Retnowati; Octo Dendy Andriyanto (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This article discusses the role of social media in increasing the popularity of Javanese music among the younger generation, against the backdrop of concerns about the decline of local culture amidst the dominance of global culture. The viral phenomenon of Javanese songs such as Satru, Widodari, and Sinarengan is an entry point to understand how local content is able to gain a place in digital popular culture. This study aims to analyze how the younger generation uses social media as a means to disseminate Javanese music and how this process contributes to the preservation and transformation of traditional culture. The method used is a literature study, by reviewing various sources such as scientific articles, online media reports, and relevant digital content. The results of the study show that the combination of Javanese lyrics and a modern presentation style is the main attraction that is able to reach a wider audience. The younger generation is not only a passive consumer, but also acts as a producer of culture by making song covers, short videos on platforms such as TikTok and YouTube, and creating new digital trends. This practice reflects a culture that is increasingly prominent in the era of social media. The role of social media has been proven to be significant in popularizing Javanese music, expanding its reach and making it part of the digital identity of the younger generation. This phenomenon shows that Javanese music is not only able to survive, but also develop through creativity that is relevant to the lifestyle of today's young generation.